Family financial behaviors - Britt, Sonya L. (My University, 2015)
The purpose of the survey was to see if any relation between relationship wellness and financial wellness existed. Knowing what, if any, interrelationship exists between relationship satisfaction and financial behaviors is necessary in order to aid the progress of relationship and financial counseling. Anticipated outcomes of the survey included discovering where people seek help and its perceived helpfulness, so that helping professionals will be able to target those places people see as most useful. A goal from this stage in my goal process was to determine how one’s personality affects his or her money management style. Unfortunately, no significant findings were found through the process of analyzing the results of the survey.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Britt, Sonya L. (2005). Family financial behaviors. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Couples--Finance, Personal; Marriage; Marriage counseling; Reports; Reports